Periodization for optimizing strength and hypertrophy; the forgotten variables - Fisher, J. P.; Steele, J.; Smith, D.; Gentil, P. (Journal of Trainology, 2018)
Objectives: A growing area of discourse within sports medicine and resistance training is that of periodization. This has been represented as variation in load and subsequently repetitions as well as volume, with a view to maximize strength and hypertrophy adaptations. A number of recent review articles have attempted to draw overarching conclusions from the present body of literature in an effort to provide definitive guidelines. However, there are numerous variables within resistance training that are often overlooked, and in the context of periodization, might significantly impact adaptation. Design & Methods: Narrative Review Results: The present piece confers need for clarity in terminology of effort rather than intensity, as well as discussing how variety of load might impact volume-load, discomfort, muscle damage and recovery. Furthermore, this article discusses often over looked variables such as variety in exercise selection, detraining periods, and supervision, which are all evidenced to impact strength and hypertrophy adaptations. Conclusions: Our opinion is that without inclusion of these variables any guidelines surrounding periodization for strength or hypertrophy are limited in application. We conclude by highlighting areas for future research, as well as practical recommendations within this field.